WhoLoDancE: digital tools and the dance learning environment - Cisneros, R. E.; Stamp, K.; Whatley, S.; Wood, K. (Research in Dance Education, 2019)
The focus of this paper is on the WhoLoDancE EU Horizon 2020 project and the tensions between the technology and the potential impact on dancer education - the aspirations versus the realities. We explore how neuroscientific concepts can help to understand the embodied experience of working with digital tools in a mediated learning environment. The paper focuses on scoping the literature that contributes to our thinking about the use of avatars and learning in the dance studio. The authors draw on neuroscience and education theory, supported by experience from developing the tools to offer insight into what technology in the dance studio could offer. We explore the possible potential for WhoLoDancE to contribute to future technologies for dance education and creation, and what opportunities might arise for teachers, learners and choreographers.